A construção das posições enunciativas à luz de relações dialógicas e alteritárias na série televisiva sessão de terapia : uma análise Bakhtiniana - Souza, Fernanda Silva de (2023)
This research presents an investigation into the construction of enunciative positions in the patient-therapist interaction in the television series Session of Therapy, observing dialogical and alteritarian relationships in the development of therapeutic encounters. Regarding the theoretical basis, we seek support in the dialogical perspective of language, developed by the Bakhtin/Volóchinov/Medviédev Circle for articulating linguistic aspects in social contexts, making it possible to verify the enunciative positions, the construction of dialogical and alteritarian relationships and the determining place of production of meanings in the discourse about life in society. In this Bakhtinian context, we developed, among others, the following concepts that subsidize the investigation: ideological sign, valuation, heterodiscourse, concrete utterance, responsive understanding, discourse genres, subject, dialogical and alteritarian relations and evaluative architecture. This research is based on the following guiding question: how are the enunciative positions constructed in the patient-therapist interaction in the television series Sessão de Terapia, observing dialogic and alteritarian relationships in possible healing paths? The general objective, in conjunction with the research question, is to investigate the construction of enunciative positions in the patient-therapist interaction in the television series Session of Therapy, observing dialogical and alteritarian relationships in possible healing paths. The specific objectives, in turn, focus on (i) verifying how the enunciative positions are established and resignified in therapeutic interactions, in view of the diversity of dialogues of voices that cross the discourse in therapy sessions; and (ii) to analyze the relationships of otherness in patient and therapist interactions in selected episodes of the Session Therapy series, observing the projection of the places occupied by the patient in her family and social life. With regard to methodological procedures, considering it to be an exploratory research, with a qualitative approach, we chose the fifth season of the series Session Therapy as analysis material, and we chose to carry out a dialogical analysis of the episodes of the patient-character Giovana in interaction with the therapist Caio. This choice was made because the patient-character presents, in utterances, aspects that, associated with the theoretical perspective adopted, establish the complexity of the I-other relationship, as marks of the constitutive alterity of subjectivity; incidence of the other's word as a resource for the construction of the patient's speech; dynamism of values in the architecture of the session: Giovana-for-Caio, Giovana-for-si and Caio-for-Giovana. The analysis follows the methodological orientation proposed by Voloshinov (2018, p. 220) which assumes the interrelation between sphere of activity, discourse genre and utterance. Given the theoretical discussions and analyzes carried out in this research, we hope to collaborate with the understanding of how therapeutic interactions occur in the Session Therapy series, in view of the different clashes of voices that build the enunciative positions and that constitute possible healing paths in the sessions focused.